2018
DOI: 10.1097/aln.0000000000002323
|View full text |Cite
|
Sign up to set email alerts
|

Processed Electroencephalogram Monitoring and Postoperative Delirium

Abstract: What We Already Know about This Topic What This Article Tells Us That Is New Background Postoperative delirium complicates approximately 15 to 20% of major operations in patients at least 65 yr old and is associated with adverse outcomes and increased resource utilization. Furthermore, patients with postoperative delirium might also be at risk of developing long-term postoperative cognitive dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 61 publications
2
57
1
1
Order By: Relevance
“…However, in the latter case, data collection might be compromised since neither event numbers nor total number of patients included in analyses match that reported by the original Chan et al article for POCD [30]. When pooling dichotomous and continuous outcomes, Mackenzie et al [17] found that electroencephalogram-guided anaesthesia was associated with a reduction in POD incidence. Luo and Zou reported similar results as Mackenzie [17] on the association of BIS-and AEP-controlled anaesthesia with POD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, in the latter case, data collection might be compromised since neither event numbers nor total number of patients included in analyses match that reported by the original Chan et al article for POCD [30]. When pooling dichotomous and continuous outcomes, Mackenzie et al [17] found that electroencephalogram-guided anaesthesia was associated with a reduction in POD incidence. Luo and Zou reported similar results as Mackenzie [17] on the association of BIS-and AEP-controlled anaesthesia with POD.…”
Section: Discussionmentioning
confidence: 97%
“…Three previous meta-analyses [15][16][17] and two systematic reviews [18,19] have investigated the association between the depth of anaesthesia and cognitive impairment. Lu et al [15] compared low BIS and high BIS groups in four studies and concluded that the depth of anaesthesia did not correlate with the risk of POCD, but deep anaesthesia carried a significantly increased risk of POD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that certain aspects of anesthetic management-including perioperative goal-directed blood flow and fluid optimization [2,3] and monitoring of the depth of anesthesia [4,5]-can have a beneficial impact on postoperative complication rates.…”
mentioning
confidence: 99%